"Thoracic migraine" as a new manifestation of migraine: Case report. (June 2018) - Kraya, Torsten; Mages, Stephan; Zierz, Stephan
Background and objectives: Abdominal pain is a well-known headache-associated symptom in migraine in children, but rarely in adults. We describe a case of a female patient with typical accompanying migraine symptoms without headache but with thoracic pain. Case report: The present case of a 41 year-old-woman shows recurrent attacks with thoracic pain and typical accompanying migraine symptoms but without headache. Symptoms resolved upon treatment with triptans and beta blockers. Discussion: This case might be interpreted as "thoracic migraine", and extends the spectrum of migraine forms. Conclusion: In patients with facial pain secondary to lung cancer, an anatomical connection between the vagal nerve, the nucleus tractus solitarii, the jugular ganglion and trigeminal system has been suggested. The present case might be an analogy to this explanation.